Prevalence of constipation in the German population – a representative survey (GECCO). Issue 3 (June 2016) - Enck, Paul; Leinert, Johannes; Smid, Menno; Köhler, Thorsten; Schwille-Kiuntke, Juliane
Background: Variable prevalence rates between 2.4 and 35% have been reported for chronic constipation across different countries worldwide, with a low 5% for Germany. Objectives and methods: We conducted a computer-assisted telephone interview among 15, 002 representative individuals in Germany, asking about health-related problems, including constipation. Those who acknowledged the presence of constipation symptoms during the preceding 12 months were questioned concerning constipation features and sociographic variables. Results: Of 15, 002 individuals interviewed, 2, 239 (14.9%) acknowledged having experienced constipation during the last 12 months, 864 (5.8%) reported constipation during the last 4 weeks, and 380 (2.5%) had current constipation symptoms; 4.4% had taken medication because of their constipation, and 2.6% had consulted a doctor for constipation. In comparison to non-constipated volunteers, those constipated had a lower health quality of life and poorer health, and lower income and social status. Conclusion: Up to 15% of the general (German) population report symptoms of constipation depending on the definition. This matches pooled constipation rates across 18 countries (14%).